Investigation on the use of fly ash as additive in optimizing cost of road pavement structure, case study at Jalan Sultan Abu Bakar, Indera Mahkota, Kuantan - Muhammad Hafeez, Hashim (2010)
Fly ash stabilization is one of the methods of soil stabilization. It is used in many fields in the world, especially in highway engineering since many years ago for changing the soil characteristics so that the soil becomes more suitable for road construction. The main objective of this study is to determine the relationship between the thickness of pavement with the percentage of fly ash and to determine the cost of pavement construction for different thickness of pavement structure. Subgrade stabilization is usually been done with addition of lots of material such as Portland Cement, lime, and bottom ash. The California Bearing Ratio (CBR) values including the addition of 4% and 8% of fly ash had been used in pavement design to determine thickness of the pavement using original sample and different percentage of additive. As the thickness of the pavement varies, the cost of constructing the road pavement structure has been calculated to get the minimum cost by comparing between the cost calculated for original, 4% and 8% of fly ash. From the CBR test result, the CBR value of the sample increase from 4.40% to 4.49% with increasing the percentages of additive. Overall, the addition of fly ash to the original sample has increased the value of CBR thus decreasing the cost of constructing the road pavement structure.